Development of an in vitro release test for the oral delivery of simvastatin-loaded alginate-chitosan microspheres - Agno, Cyra Marie P.; Barlis, Kyla Angeli T.; Bulatao, Bryan Paul I.; Tandoc, Jewel M. (Manila Department of Pharmacy, College of Pharmacy, University of the Philippines Manila, 2025)
Existing guidelines for drug release testing are mainly designed for conventional oral and transdermal dosage forms. While some attempts have been made to extend these guidelines to novel drug delivery systems (DDS), they often fail to consider the distinct characteristics that set these systems apart from traditional formulations. Therefore, establishing a suitable drug release testing method for microparticles is crucial for optimizing these innovative delivery systems and for generating essential data to support the development of robust compendial and regulatory standards. In this study, simvastatin-loaded alginate chitosan microspheres (SMV-ALG/CS MS) were formulated and characterized for encapsulation efficiency (EE%) and drug loading capacity (LC%). Equilibrium solubility studies were conducted using simulated gastric (SGF) and intestinal (SIF) fluids as the release media containing various concentrations of Tween 80 (0.5%, 1.0%, 2.0%, and 3.0% v/v) to determine the minimum volume required to achieve sink conditions. The release profile of the prepared MS was then determined using the developed in vitro release testing method. The SMV-ALG/CS MS demonstrated an EE of 37.85% and an LC of 10.75%. The medium containing 3.0% v/v Tween 80 achieved sink conditions with the smallest required volume. However, in vitro drug release testing revealed an initial burst release in SGF, indicating that the formulation did not show a delayed-release profile. Furthermore, the final cumulative release of 241.07% was inconsistent with the microspheres' LC, possibly caused by inadequate cross-linking, high surfactant concentration, and erratic absorbance readings by the UV/Vis Spectrophotometer.
Thesis (Bachelor of Science in Pharmaceutical Sciences)--University of the Philippines Manila, June 2025
Keywords: Controlled release preparations -- Alginate-chitosan microspheres -- Pharmaceutical evaluation; Simvastatin -- Oral drug delivery -- In vitro characterization; Drug delivery systems -- Microspheres -- In vitro release testing -- Simvastatin